Teaching anatomy in the XXI century: New aspects and pitfalls - Papa, V.; Vaccarezza, Mauro (Hindawi Publishing Corporation, 2013)
Anatomy has historically been a cornerstone in medical education regardless of nation, racial background, or medical school system. By learning gross anatomy, medical students get a first “impression” about the structure of the human body which is the basis for understanding pathologic and clinical problems. Although the importance of teaching anatomy to both undergraduate and postgraduate students remains undisputed, there is currently a relevant debate concerning methods of anatomy teaching. In the past century, dissection and lectures were its sole pedagogy worldwide. Recently, the time allocated for anatomy teaching was dramatically reduced to such an extent that some suggest that it has fallen below an adequate standard. Traditional anatomy education based on topographical structural anatomy taught in lectures and gross dissection classes has been replaced by a multiple range of study modules, including problem-based learning, plastic models or computer-assisted learning, and curricula integration. “Does the anatomical theatre still have a place in medical education?” And “what is the problem with anatomic specimens?” We endeavor to answer both of these questions and to contribute to the debate on the current situation in undergraduate and graduate anatomy education.